(3fRgI GdeSJeY hGddGaX aj efGbH GdTjN eMeO GdMGaXs - (3eMeOj Hf SjOfG GdYdhj, HOjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3Ydi QCSg hdOGf fjd ehGUdJge hjSJbhfg HcCS GdeMHI HcCS QbGFbge eY aJjGf ETGQJge Ydi HSGW UaGA NhGWQge aEf ScQ MLHhg ZjQI Ydi GdEaTGA dCSQGQge s
(3BNQgG (B:s
(3EYde QMec Gddg JYGdi Cfi dG CSJhai eG dTjNfG hSjOfG hehdGfG CMeO GdJLGfi ef GdeBKQ hGdBjGJ hGdcQGeGJ CHO GdBHOjf hOgQ GdOGgQjf hbO bdJ ai Pdc ef bUjOI CeOMg HgG s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JGQjN (B2737) s
Keywords: (3GdJGQjNs